Mulheres na política: análise dos perfis femininos das candidatas nas eleições 2022 para a Câmara Federal - Fratini, Juliana (2023)
TThe present study proposes to investigate the reasons for female underrepresentation in Brazilian politics in the timeline from social, cultural and systemic electoral aspects, in addition to the variables that most contribute to the eligibility of candidates. For this, different research methods were used, namely the bibliographic review, the comparative study, the survey of quantitative and qualitative data and the case study from the 2022 elections for the Federal Chamber. Through the bibliographic review and the collected data, it was identified the persistence of the electorate in opting for candidacies with very specific characteristics, with a conservative profile, both for men and women. That is, the more conservative the candidacies, the more chances of victory or electoral success they tend to have, even though the profile of the Federal Chamber elected in 2022 does not match the self-identified portrait by Brazilians themselves in the last sociodemographic survey carried out by the IBGE. The discussion held here concerns female underrepresentation in quantitative and qualitative terms and how deficits can be mitigated through various actions when there is a search for an ideal representative government in which women also occupy power